A Patient with Monoclonal Gammopathy of Undetermined Significance and Detected Philadelphia Chromosome - Tran Truc; Cai Jennifer; Ji Ping; Qing Xin (Journal of Hematology and Oncology Research, 2022)
Background Monoclonal gammopathy of undetermined significance (MGUS) and chronic myeloid leukemia (CML) are diseases of different lineages. The diagnosis of both MGUS and CML in the same patient is a rare occurrence and has not been reported in much literature. Case Presentation We describe a 56-year-old man with a history of rheumatoid arthritis incidentally found to have an increase in IgA paraprotein. With less than 10% monoclonal plasma cells on the bone marrow biopsy and absence of hypercalcemia, renal failure, anemia and bone lesions, MGUS was diagnosed. The conventional cytogenetics at the time showed the presence of the Philadelphia chromosome in 30% of metaphases. However, there was no morphologic evidence of CML in the peripheral blood or bone marrow. Patient received no treatment and lost follow-up until 3 years later when a routine CBC showed leukocytosis and thrombocytosis. CML, chronic phase was diagnosed following a bone marrow aspiration and biopsy with Philadelphia chromosome observed in 100% of metaphases. Patient was treated with imatinib and later switched to dasatinib and complete molecular remission was continued to be achieved. Discussion and Conclusion Here we report a case of pre-leukemic CML as an incidental finding during the diagnosis of MGUS. The possible underlying mechanisms of the association are discussed although the exact cause of the coexistence is unclear.
Keywords: Monoclonal gammopathy of undetermined significance